Digitalisasi dan Perubahan Sosial Budaya Masyarakat Urban - Hidayatullah, Muhammad Arif (Rayhan Intermedia, 2024)
Urbanization and the development of cities not only have an impact on economic aspects, but also bring significant socio-cultural changes. Digitalization also affects the values and social norms of urban society. In cities, traditional values are often replaced by more pragmatic modern values. Descriptive qualitative research aims to provide a thorough description of events, environments, or phenomena in a particular situation without manipulation. The socio-cultural impacts of urbanization reflect the complexity and dynamics of life in big cities. While urbanization brings many benefits, such as access to better education and jobs, it also presents challenges that affect people's social values, norms and lifestyles.